2020
DOI: 10.1016/j.clbc.2020.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the COVID-19 Pandemic on Surgical Breast Cancer Care in the Netherlands: A Multicenter Retrospective Cohort Study

Abstract: Background Coronavirus disease 2019 (COVID-19) has put a strain on regular healthcare worldwide. In the Netherlands, the national screening programs, including for breast cancer, were halted temporarily. This posed a challenge to breast cancer care, because ∼40% of cases are detected through national screening. Therefore, the aim of the present study was to evaluate the effects of the COVID-19 pandemic on the surgical care of patients with breast cancer in the Netherlands. Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 25 publications
5
69
1
2
Order By: Relevance
“…No statistically significant changes were observed in the overall scores of the Breast-Q, SF-36 and EQ-5D-5L questionnaires at baseline compared to 2 weeks, 3 and 6 months after ductoscopy, indicating that ductoscopy does not negatively influence QOL. These findings further support the use of ductoscopy, which is performed more and more for both diagnostic and therapeutic purposes [ 26 , 34 , 35 ]. Additionally, this study showed that the all domains of Breast-Q, and EQ-5D-5L were stable over time and are thereby useful questionnaires for PND patients, while SF-36 was as a whole less useful and would require modifications.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…No statistically significant changes were observed in the overall scores of the Breast-Q, SF-36 and EQ-5D-5L questionnaires at baseline compared to 2 weeks, 3 and 6 months after ductoscopy, indicating that ductoscopy does not negatively influence QOL. These findings further support the use of ductoscopy, which is performed more and more for both diagnostic and therapeutic purposes [ 26 , 34 , 35 ]. Additionally, this study showed that the all domains of Breast-Q, and EQ-5D-5L were stable over time and are thereby useful questionnaires for PND patients, while SF-36 was as a whole less useful and would require modifications.…”
Section: Discussionsupporting
confidence: 61%
“…A meta-analysis showed that ductoscopy has a sensitivity of 94% in detecting intraductal lesions of any type, but cannot reliably discriminate between benign and malignant lesions [ 46 ]. Another network meta-analysis showed that ductoscopy has a significantly higher diagnostic accuracy than MRI for the detection of malignancy in patients with PND and negative ultrasound and/or mammography [ 47 ]. Therefore, ductoscopy is more useful when conventional imaging is negative [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations